Opting out from public services and the social contract in Latin America - Ana L. De La O; Cecilia Rossel Odriozola; Pilar Manzi (Inter-American Development Bank (IDB), 2023)
The seemingly upward trend in opting out from public services and the segregation of income groups in public and private education and health systems has raised concerns about the future of an already fragmented social contract in Latin America. In this chapter, we examine the evolution of the use of private education and private health insurance in selected countries during the first two decades of the 2000s. We also examine the socio-demographic correlates of the decision to opt out, and the association it has with attitudes that are relevant to understand the foundations of the social contract in the region. Overall, the evidence suggests that scholars' concerns about the fragility of the social contract are justified, but with some nuances. Wealthy households are mostly opting out of the public education system, and the middle-class is split with a substantial proportion of households opting for private schools. On the other hand, opting out from public health is only prevalent among wealthy households, and even within that group the share of households who are paying for a private health insurance is much smaller than the share of households who opt for private education. For both policy domains, however, we find that people who use private services have worse evaluations of public services, express less support for the public provision of those services, and more generally, are less supportive of redistribution compared to people inside the public systems. We discuss the implications of these descriptive statistics for the sustainability of the public provision of services and the social contract.
Keywords: I1; I2; I3; 330; opting out; education; health; inequality; social contract; inequality; Latin America